The Improving Speaking Skills through Active Learning Strategy - Hasan, Hasan; Kahar, Abd; Hermansyah, Sam; Usman, Usman (Maspul Journal of English Studies, 2021)
This research aimed at proving that active learning strategy can improve the speaking skill of the year eight students of SMP Negeri 1 Sidrap. The researcher used pre-experimental design. The population of this research was the eighth grade students and the sample was class B consisting of 26 students. The sample was chosen by purposive sampling technique. The data were collected through oral test. The pre-test and the post-test were used to measure the improvement of the students‟ speaking skill before and after the treatment. Based on the result of the pre-test and the post-test, it is obtained that the t-counted value is 6.920. By applying 0.05 level of significance and the 25 (26-1) degree of freedom, it was found that t-table value is 2.060. It shows that the t-counted value is greater than the t-table value. It means that the use of active learning strategy can improve speaking skill of the year eight students of SMP Negeri 1 Sidrap.